Language, Culture, and Gender: The Role of Traditional Stories in the Acceptance of Transgender Individuals - Anthony M. Mon; Elmer C. Diocares; Shella Marie I. Diocares (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This qualitative study investigates the intersection of traditional storytelling, cultural heritage, and the societal acceptance of transgender individuals within the Philippine context. While historical narratives often dictate rigid gender binaries, this research explores how such stories can simultaneously act as barriers to and instruments for gender inclusivity. Through semi-structured interviews with eight transgender participants from Sta. Cruz, Zambales, the study identifies core thematic challenges, including religious discrimination, deep-seated superstitions regarding "bad luck," and the pervasive influence of gendered role performance. The findings suggest that while traditional narratives currently reinforce stereotyping and misinformation, they possess the latent power to reshape social values. By promoting inclusive storytelling and leveraging family support systems, society can transition from exclusionary traditions toward a framework of empathy, self-love, and genuine transgender integration.